Screening, Identification, and Fermentation of Brevibacillus laterosporus YS-13 and Its Impact on Spring Wheat Growth - Wenjing Zhang; Xingxin Sun; Zele Wang; Jiayao Li; Yuanzhe Zhang; Wei Zhang; Jun Zhang; Xianghan Cheng; Peng Song (Microorganisms, 2025)
The low availability of phosphorus (P) in soil has become a critical factor limiting crop growth and agricultural productivity. This study aimed to isolate and evaluate a bacterial strain with high phosphate-solubilizing capacity to improve soil phosphorus utilization and promote crop growth. A phosphate-solubilizing bacterium, designated as YS-13, was isolated from farmland soil in Henan Province, China, and identified as Brevibacillus laterosporus based on morphological characteristics, physiological and biochemical traits, and 16S rDNA sequence analysis. Qualitative assessment using plate assays showed that strain YS-13 formed a prominent phosphate solubilization zone on organic and inorganic phosphorus media containing lecithin and calcium phosphate, with D/d ratios of 2.28 and 1.57, respectively. Quantitative evaluation using the molybdenum–antimony colorimetric method revealed soluble phosphorus concentrations of 21.24, 6.67, 11.73, and 17.05 mg·L−1 when lecithin, ferric phosphate, calcium phosphate, and calcium phytate were used as phosphorus sources, respectively. The fermentation conditions for YS-13 were optimized through single-factor experiments combined with response surface methodology, using viable cell count as the response variable. The optimal conditions were determined as 34 °C, 8% inoculum volume, initial pH of 7.55, 48 h incubation, 5 g L−1 NaCl, 8.96 g L−1 glucose, and 8.86 g L−1 peptone, under which the viable cell count reached 6.29 × 108 CFU mL−1, consistent with the predicted value (98.33%, p < 0.05). The plant growth-promoting effect of YS-13 was further validated through a pot experiment using Triticum aestivum cv. Jinchun 6. Growth parameters, including plant height, fresh biomass, root length, root surface area, root volume, and phosphorus content in roots and stems, were measured. The results demonstrated that YS-13 significantly enhanced wheat growth, with a positive correlation between bacterial concentration and growth indicators, although the growth-promoting effect plateaued at higher concentrations. This study successfully identified a high-efficiency phosphate-solubilizing strain, YS-13, and established optimal culture conditions and bioassay validation, laying a foundation for its potential application as a microbial inoculant and providing theoretical and technical support for reducing phosphorus fertilizer inputs and advancing sustainable agriculture.